Peran Mediasi Thriving at Work pada Pengaruh Proactive Personality terhadap Career Adaptability - Muhammad Agung Prasetyo Wibowo; IBG Adi Permana (Forum Inovasi Bisnis dan Manajemen, 2019)
Career adaptability is one of the resource that must be possessed by every person on this day, because it has been considered as a driving factor that help people to achieve the desired work goals. Moreover, nowadays it has been known that the work arrangements are unpredictable and too many changes that occurs, because it is considered to have no boundaries and transparent, one of them is the emergence of new job relationships such as internet freelance. Antacedents that have been known previously from career adaptability are widely known as proactive personality, then This study also discuss another antecedent for career adaptability, which is known as thriving at work. This study also confirms previous research that discuss the mediating role of thriving at work on the effect of proactive personality on career adaptability. Total of the sample on this study are 352 internet freelancers from an online employement platform in Indonesia, where the internet freelance responded to the questionnaire that was shared by the author through an online approach. The obtained data have been analyzed by conducting a simple regression test equipped with PROCESS Model 4. Result have shown that there is a significant direct relationship of the three variables raised in this study, then also revealed the role of mediating from thriving at work on the effect of proactive personality on career adaptability. Overall, this study contributes to the literature discussing internet freelance.